An update on adjunctive treatment options for bipolar disorder. (25th January 2018) - Dean, Olivia M; Gliddon, Emma; Van Rheenen, Tamsyn E; Giorlando, Francesco; Davidson, Sandra K; Kaur, Manreena; Ngo, Trung T; Williams, Lana J
Abstract : Objectives: Bipolar disorder is a complex illness often requiring combinations of therapies to successfully treat symptoms. In recent years, there have been significant advancements in a number of therapies for bipolar disorder. It is therefore timely to provide an overview of current adjunctive therapeutic options to help treating clinicians to inform their patients and work towards optimal outcomes. Methods: Publications were identified from PubMed searches on bipolar disorder and pharmacotherapy, nutraceuticals, hormone therapy, psychoeducation, interpersonal and social rhythm therapy, cognitive remediation, mindfulness, e‐Health and brain stimulation techniques. Relevant articles in these areas were selected for further review. This paper provides a narrative review of adjunctive treatment options and is not a systematic review of the literature. Results: A number of pharmacotherapeutic, psychological and neuromodulation treatment options are available. These have varying efficacy but all have shown benefit to people with bipolar disorder. Due to the complex nature of treating the disorder, combination treatments are often required. Adjunctive treatments to traditional pharmacological and psychological therapies are proving useful in closing the gap between initial symptom remission and full functional recovery. Conclusions: Given that response to monotherapy is often inadequate, combination regimens for bipolar disorder are typical. Correspondingly, psychiatric research is working towards a better understanding of the disorder's underlying biology. Therefore, treatment options are changing and adjunctive therapies are being increasingly recognized as providing significant tools to improve patient outcomes. Towards this end, this paper provides an overview of novel treatments that may improve clinical outcomes for people with bipolar disorder.